Was the New Deal contractionary? - Gauti B. Eggertsson (Federal Reserve Bank of New York, 2006)
Can government policies that increase the monopoly power of firms and the militancy of unions increase output? This paper studies this question in a dynamic general equilibrium model with nominal frictions and shows that these policies are expansionary when certain “emergency” conditions apply. I argue that these emergency conditions— zero interest rates and deflation—were satisfied during the Great Depression in the United States. Therefore, the New Deal, which facilitated monopolies and union militancy, was expansionary, according to the model. This conclusion is contrary to the one reached by Cole and Ohanian (2004), who argue that the New Deal was contractionary. The main reason for this divergence is that the current model incorporates nominal frictions so that inflation expectations play a central role in the analysis. The New Deal has a strong effect on inflation expectations in the model, changing excessive deflation to modest inflation, thereby lowering real interest rates and stimulating spending.
Keywords: E52; E62; E65; N12; 330; Great Depression; New Deal; National Industrial Recovery Act; zero interest rates; deflation; Marktmacht; Monopol; Gewerkschaft; Dynamisches Gleichgewicht; Wirtschaftspolitik; Wirtschaftskrise; USA; Verhandlungsmacht